The Development and Validation of Turkish Version of the Elementary Teachers' Efficacy and Attitudes towards STEM (ET-STEM) Scale - Emine Sahin-Topalcengiz; Bekir Yildirim (Seyit Ahmet Kıray, 2019)
The purpose of this study was to adapt the Elementary Teachers Efficacy and Attitudes towards STEM Survey (ET-STEM scale; Friday Institute for Educational Innovation, 2012) into Turkish and test the validity and reliability of the instrument. ET-STEM was administered to 313 elementary teachers from different provinces of Turkey. Exploratory and confirmatory factor analyses were conducted to examine the structural validity of the scale. According to exploratory factor analysis results, the ET-STEM survey consists of nine factors. The values of Cronbach's alpha of the factors ranged from 0.891 to 0.964, and corrected item-total scale correlation ranged from 0.313 to 0.417. After the exploratory factor analysis performed, the ET-STEM was administered to 213 elementary school teachers. The results obtained from the confirmatory factor analyses demonstrated adequate reliability and validity for measuring the STEM competencies and attitudes of elementary school teachers.